Finite element simulation on heterogeneous material - Ang, Teck Khiang (2019)
In the present, the study of effective elastic modulus and Poisson’s ratio of a two – phase bi – continuous heterogenous material is estimated using finite element methods. The microstructure of such material are unknown since the two phases of the bi – continuous heterogenous materials are generally random could not be clearly identified. The microstructure can be constructed by means of finite element mesh where materials are randomly allocated into the elements. With that, the effective elastic modulus and Poisson’s ratio can be obtained by running a number of simulations. This method has been proven reliable and accurate for a bi – continuous heterogenous material by Xu et al. (2009). Utilizing a two – phase bi – continuous heterogenous material with a vast difference of material properties as the focus, the study will examine how the specimen size, element density would affect the effective elastic modulus and Poisson’s ratio of the bi – continuous material. It can be observed that as the element density increases, the results converges and thus, increasing the accuracy of the effective elastic modulus and Poisson’s ratio presented. After determining element density required to provide an accurate result, the study would proceed to investigate effective elastic modulus and Poisson’s ratio by varying the volume fraction and domain sizes of the two constituent materials of the specimen. In conclusion, the method and simulation procedures presented in the numerical study is able to provide an estimation of the effective elastic modulus and Poisson’s ratio with acceptable accuracy.